Identification of Deep Groundwater Aquifer Zones with Geoelectrical Method in Sukadanaham Area Bandar Lampung, Indonesia - Haerudin, Nandi; Rizkiano, Aldika; Mulyasari, Rahmi; Hesti (UIR PRESS, 2024)
Research on groundwater aquifers using the geoelectric method has been carried out in the Sukadanaham area, Tanjung Karang Barat District, Bandar Lampung City. This Research Objectives This research aims to identify the lithology and depth of groundwater aquifer zones based on resistivity values ​​and geological literature. Data acquisition was carried out using the Schlumberger configuration of 3 points in the young Betung volcanic formation (Qhvb). The data used is the resistivity value. Resistivity value data is modeled vertically with inverted results. The resistivity value of each point is adjusted and interpolated based on the literature on rock resistivity values. Based on the identification results, 4 types of subsurface rock lithology were found, namely top soil, tuff, breccia, and andesite. The lithology of the layers at point 1, point 2 and point 3 is dominated by tuff and breccia layers. The resistivity value of the andesite layer obtained has a high value, which is > 300 Ωm. The resistivity value of the tuff layer for the waterproof layer has a value of 200-250 Ωm. The breccia layer acts as a groundwater aquifer zone with a low resistivity value of 15-60 Ωm. The rock resistivity value with the lowest value is at a depth of 40-95 m which is a compressed aquifer layer with andesite and tuff layers as a waterproof layer above and below.